Heart rate variability and amplitude-integrated electroencephalography measured shortly after birth and time to reach clinical milestones: a pilot study in late preterm infants - Birju A. Shah; Samantha Latremouille; Sanjay Chawla; Martin Keszler; Richard Tucker; Abbot Laptook; Guilherme M. Sant'anna (Frontiers in Pediatrics)
BackgroundAmong late preterm (LPT) infants, there is significant variability in reaching milestones for safe discharge. We examined the associations of early measures of heart rate variability (HRV) and amplitude-integrated electroencephalogram (aEEG) with time to wean to an open-air cot and to achieve full oral feeds.MethodsThis is a prospective, multicenter observational cohort study that enrolled infants between 340/7 and 346/7 weeks gestational age (GA). Infants with growth restriction and major congenital anomalies were excluded. Electrocardiogram (ECG) for 1 h and cross-cerebral aEEG for 6 h were recorded within 96 h after birth. Correlations of HRV and aEEG parameters with outcomes were evaluated using stepwise linear regression.ResultsOf the 26 infants from three centers, 23 were included for analysis for time to an open-air cot. The analysis for time to full oral feeds was limited to 19 infants from two centers with similar feeding policies. Including HRV parameters (time domain, median and standard deviation of R-wave to R-wave interval; frequency domain, ratio of the low frequency to high frequency power and their interaction) and aEEG parameters (total and immature cycles/hour) strengthened associations with time to open-air cot (adjusted R2 = 0.72) and time to full oral feeds (adjusted R2 = 0.53) compared with each parameter alone.ConclusionsEarly measurements of HRV and aEEG parameters correlate with time to an open-air cot and to achieve full oral feeds in LPT infants born between 340/7 and 346/7 weeks GA.